Principles of Resonance Energy Transfer. Issue 12 (12th December 2022) - Szabó, Ágnes; Szöllősi, János; Nagy, Peter
Abstract: This unit describes the basic principles of Förster resonance energy transfer (FRET). Beginning with a brief summary of the history of FRET applications, the theory of FRET is introduced in detail using figures to explain all the important parameters of the FRET process. After listing various approaches for measuring FRET efficiency, several pieces of advice are given on choosing the appropriate instrumentation. The unit concludes with a discussion of the limitations of FRET measurements followed by a few examples of the latest FRET applications, including new developments such as spectral flow cytometric FRET, single‐molecule FRET, and combinations of FRET with super‐resolution or lifetime imaging microscopy and with molecular dynamics simulations. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. This article was corrected on 20 December 2022. See the end of the full text for details.